Intra- and extracellular β-amyloid overexpression via adeno-associated virus-mediated gene transfer impairs memory and synaptic plasticity in the hippocampus - Forner, Stefania; Martini, Alessandra; Prieto, Gilberto Aleph; Dang, Cindy; Rodriguez-Ortiz, Carlos; Reyes Ruiz, Jorge Mauricio; Trujillo-Estrada, Laura Isabel; da Cunha, Celia; Andrews, Elizabeth; Phan, Jimmy; Ha, Jordan; Chang, Allissa; et al. (Springer Nature, 2019)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is currently conceptualized as a disease of synaptic failure. Synaptic impairments are robust within the AD brain and better correlate with dementia severity when compared with other pathological features of the disease. Nevertheless, the series of events that promote synaptic failure still remain under debate, as potential triggers such as β-amyloid (Aβ) can vary in size, configuration and cellular location, challenging data interpretation in causation studies. Here we present data obtained using adeno-associated viral (AAV) constructs that drive the expression of oligomeric Aβ either intra or extracellularly. We observed that expression of Aβ in both cellular compartments affect learning and memory, reduce the number of synapses and the expression of synaptic-related proteins, and disrupt chemical long-term potentiation (cLTP). Together, these findings indicate that during the progression AD the early accumulation of Aβ inside neurons is sufficient to promote morphological and functional cellular toxicity, a phenomenon that can be exacerbated by the buildup of Aβ in the brain parenchyma. Moreover, our AAV constructs represent a valuable tool in the investigation of the pathological properties of Aβ oligomers both in vivo and in vitro.
Keywords: Alzheimer, Enfermedad de; Alzheimer's disease; amyloid beta; Synaptic plasticity; Dendritic spines